Reorganization and outplacement in the interest of competitiveness - Chovan, Brigitta; Poór, József (Studia Mundi – Economica, 2017)
In the current state of economy, a company has a perspective only if it is able to adapt itself to these changes in a competitive and effective way through flexible restructuring, and building relevant strategies and systems. The success of the HR function depends on its ability to create value through the business activity as well as to lead the reorganization strategy and outplacement process that is necessary for business success.The aim of the research is to study the role of reorganization process implementations and outplacement in the increasing of business competitiveness.What makes the research important and actual is that the created “Best Practice” gives a guide about what strategies and methods HR professionals can apply to increase business competitiveness that is getting more and more emphasis nowadays.